2017
DOI: 10.1016/j.geomorph.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of marine radar to monitoring seasonal and event-based changes in intertidal morphology

Abstract: This paper demonstrates the application of marine radar and a newly developed waterline mapping technique to the continued surveillance and monitoring of inter-and intra-annual intertidal morphological change, thus capturing new detail on coastal system behaviours. Marine radar data from 2006-2009 are used to create a sequence of waterline elevation surveys that show clear morphological evolution of two different sites in the Dee estuary, UK. An estimate of volumetric change was made at two locations: West Hoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…The main limitation of the SED-sensors is that they take point measurements. Future studies could combine marine radar technology with SED-sensors to explore tidal flat dynamic equilibrium behaviours over larger scales while maintaining high monitoring resolution (Bell et al, 2016;Bird et al, 2017), and thus lead to improvements in current understanding of DET and morphological modelling.…”
Section: Direct Field Evidence Supporting Detmentioning
confidence: 99%
“…The main limitation of the SED-sensors is that they take point measurements. Future studies could combine marine radar technology with SED-sensors to explore tidal flat dynamic equilibrium behaviours over larger scales while maintaining high monitoring resolution (Bell et al, 2016;Bird et al, 2017), and thus lead to improvements in current understanding of DET and morphological modelling.…”
Section: Direct Field Evidence Supporting Detmentioning
confidence: 99%
“…Furthermore, this method was adopted by Wang et al [58], and its performances to fill the gaps in a global soil moisture dataset was analyzed. Recently, Bell et al [28] and Bird et al [29] have employed this algorithm to fill the gaps in beach profile data. This The mTWM with corrected wave run-up is applied to all alongshore locations to determine the spatio-temporal variation in shoreline positions for the entire study area over the period between April 12, 2005 andDecember 31, 2008, as shown in Figure 22.…”
Section: Shoreline Position Data Gaps Filled By Garcia's Methodsmentioning
confidence: 99%
“…Time-series of individual radar pixel intensities are gathered from hourly time-averaged images across the selected timescale of two weeks, including a full spring-neap cycle (as an example, June [17][18][19][20][21][22][23][24][25][26][27][28][29][30]2005). Figure 6a displays the cross-shore time stack images within the range between y = 5 m and y = 103 m. The red line marked in Figure 6b indicates the variation of the instantaneous waterline position digitized manually by visual inspection, and Figure 6c is the concurrent tidal records.…”
Section: Intertidal Beach Profile and Shoreline Estimation Using Twm mentioning
confidence: 99%
See 2 more Smart Citations